Magnetic Characterization Techniques for Nanomaterials - Kumar, Challa S.S.R (Springer Berlin Heidelberg : Imprint: Springer, 2017)
Sixth volume of a 40 volume series on nanoscience and nanotechnology, edited by the renowned scientist Challa S.S.R. Kumar. This handbook gives a comprehensive overview about Magnetic Characterization Techniques for Nanomaterials. Modern applications and state-of-the-art techniques are covered and make this volume an essential reading for research scientists in academia and industry.
Keywords: Materials science.; Nanochemistry.; Nanotechnology.; elektronické knihy; electronic books